Analisis Sub Sektor Unggul Pertanian di Kabupaten Lamongan dan Kabupaten Tuban - Burhanudin Yusuf Hanafi; Wiwin Priana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The most successful agricultural sub-sectors in Lamongan and Tuban districts are the subjects of this study. In Lamongan and Tuban districts, agriculture is the most significant industry. Agriculture, forestry, and fisheries, as well as energy and gas procurement, clean water, waste management, construction, and wholesale and retail trade, have the potential to become basic industries in Lamongan Regency. Automotive repair, information technology (ICT), military cooperation and manufacturing are some of the other sectors in the area. Lamongan Regency has a population of 200,000 people. Agriculture, forestry and fisheries account for an average of 2.9 percent of basic sector production. Agriculture is one of the fastest growing businesses in the United States, according to shift share data. are in the second or third best quadrant. There are several industries in Tuban Regency that can become the backbone of the economy. These industries include food production and forestry as well as fisheries and mining. Tuban Regency can also be at the forefront in the fields of technology, defense, government administration, and social security. Agriculture, forestry, and fisheries make up the majority of the output of the fundamental sector. By shifting share, agriculture is one of America's fastest growing businesses. They are in the upper quartile, which indicates that they are very good. Keywords: Location Quotient Analysis, Shift Share, Klassen Typology